Blind Image Blur Identification in Cepstrum Domain - Shiqian Wu; Zhongkang Lu; Ee Ping Ong; Weisi Lin (2007 16th International Conference on Computer Communications and Networks, 2007)
The type and extent of blur affect image quality and therefore its evaluation. This paper presents an accurate method for blur identification and parameter estimation from one image without a priori knowledge. The key idea of the proposed method is to perform Fourier transform of logarithm spectrum to detect the periodic blur pattern in cepstrum domain instead of spectral nulls. Accordingly, the estimation of blur parameters is more accurate and robust to noise. The experimental results validate the accuracy of the proposed method.